Disability‐based discrimination and health: findings from an Australian‐based population study - Lauren Krnjacki; Naomi Priest; Zoe Aitken; Eric Emerson; Gwynnyth Llewellyn; Tania King; Anne Kavanagh (Elsevier, 2018)
Abstract Objective: Among working‐age Australian adults with a disability, we assess the association between disability‐based discrimination and both overall health and psychological distress. Methods: Using data from the 2015 Australian Bureau of Statistics Survey of Disability, Ageing and Carers we estimated the proportion of working‐age women and men (15-64 years) with disability who report disability‐based discrimination by socio‐demographic characteristics and assessed the association between disability‐based discrimination and self‐reported health and psychological distress. Results: Nearly 14% of Australians with disability reported disability‐based discrimination in the previous year. Disability‐based discrimination was more common among people living in more disadvantaged circumstances (unemployed, low income, lower‐status occupations), younger people and people born in English‐speaking countries. Disability‐based discrimination was associated with higher levels of psychological distress (OR: 2.53, 95%CI: 2.11, 3.02) and poorer self‐reported health (OR: 1.63, 95%CI: 1.37, 1.95). Conclusion: Disability‐based discrimination is a prevalent, important determinant of health for Australians with disability. Implications for public health: Disability‐based discrimination is an under‐recognised public health problem that is likely to contribute to disability‐based health inequities. Public health policy, research and practice needs to concentrate efforts on developing policy and programs that reduce discrimination experienced by Australians with disability.